Polskojęzyczne podręczniki i komentarze do skodyfikowanego prawa małżeńskiego Kościoła Łacińskiego i Kościołów Wschodnich Część II - Góralski, Wojciech (Ius Matrimoniale, 2016)
The circumstances of promulgating in 1983 by John Paul II of the new Canon Law shaped in the spirit of science and the guidelines of the Second Vatican Council, which was raising interest of canonist, prompted deeper studies over its norms, also in the sphere of marital law. Marital law has been amended and modifies since the Code of 1917, which was clear from the post-Council law and intense work of the Papal Commission on Revision of CIC. In that period of time several comprehensive manuals and commentaries appeared (in Polish) to the marital law included in CIC by: T. Pawluk, E. Sztafranowski, W. Góralski, J. Krukowski, M. Żurowski, P. Gajda and P. Majer. The authors of the manuals and commentaries to the marital law included in CCEO are W. Góralski and K. Nitkiewicz.